Fundholding in northern region: the first year. Issue 6874 (6th February 1993) - Newton, J; Fraser, M; Robinson, J; Wainwright, D
Abstract : OBJECTIVE--To describe the experiences of 10 fundholding practices in the Northern region during 1991-2 and to elicit subjective assessments of the impact of their change in status on practice management and patient care. DESIGN--Semistructured interviews were conducted with clinicians and practice managers; other staff in the practices were asked to fill in questionnaires. Questions were asked about the preparatory year, the impact of fundholding on clinical practice and practice management, perceptions of the costs and benefits of fundholding, and views about the future of the scheme. SETTING--10 of the 28 first wave fundholding practices in the Northern region, March-July 1992. RESULTS--Two interviews were conducted in nine practices and one interview in the tenth practice. Replies to the questionnaire were received from 35 general practitioners (73%) and 89 (58%) nonmedical staff. Practices sought independence in applying for fundholding status and found the preparatory year challenging and time consuming. General practitioners thought that the greatest change had occurred in relationships with consultants and the least change in relationships with patients. Most respondents thought that fundholding had changed the way they worked. The perceived benefits of fundholding were mentioned more often than the perceived costs. CONCLUSIONS--The results offer some encouragement to the proponents of fundholding, but more longitudinal studies are needed to evaluate the misgivings of critics of the scheme. Fundholders are uncertain about their ability to make savings year after year, particularly in an increasingly cost contained environment.